Influence of customer expectations and service encounter on perception of service quality in fast food retailing (2000)
"The influence of customer expectations and service encounter on perception of service quality in fast food retailing was investigated in this study, using 196 patrons of three fast food outlets in Oshodi-Jsolo Local Government Area of Lagos State. The instrument used for data collection consisted of three different scales; service encounter scale: customers' expectation scale, and perception of quality scale. A 2*2 analysis of variance and independent t-test were used to analyse the data. The results showed that there was interactive effect of service encounter and customers expectations on perceived service quality. (F1, 108=5.54;P<(0.05) . However, there was no difference in the perceived service quality of males and females (t=0.13;df=1 94.n.s). The findings of this study reveals that there are implications for consumer psychologists fast food operators, it also emphasized the need for proper training of outlet staff to deliver quality service and the provision of an enabling service climate "